The Impact of Social Justice and Alienation on Political Participation in Jahrom City - Gerami, Masoud; Rasekh, Keramatollah; Karimi, Majidreza (Cuestiones Políticas, 2020)
The purpose of this research is to study the impact of social justice and alienation on the political participation of people in Jahrom, Iran. Methodologically, field surveys were applied in terms of amplitude, and a cross-sectional study in terms of scope. The statistical population of this research were the holders of voting rights (over 18 years old) residing in the city of Jahrom. Sample size was calculated using the Cochran formula and selected by simple multi-stage cluster random sampling. The research questionnaire was developed by an investigator and was used by experts to determine its validity. For the data analysis, the regression coefficient tests, Mann-Whitney and Kruskal-Wallis were used. The results showed that there is a significant relationship between the sense of social justice and the sense of social alienation with political participation among the citizens of Jahrom. Furthermore, according to the study findings, the relationship of political participation based on contextual factors of citizens, gender, marital status, income, occupation and social class did not have a significant correlation with political participation (P value> 0.5).